Staphylococcus aureus Augments Epithelial Skin Barrier Damage Through T Cell Activation in Cutaneous T Cell Lymphoma - Gluud, Maria; Pallesen, Emil M.; Zeng, Ziao; Namini, Martin R. J.; Vadivel, Chella Krishna; Gjerdrum; Lise Mette Rahbek; Yan, Lang; Ahmad, Sana; Lindahl, Lise M.; Bzorek, Michael; Kamstrup, Maria R.; et al. (Wiley-Blackwell, 2026)
Background
Skin barrier dysfunction is central to inflammation and susceptibility to infection in atopic dermatitis (AD). Cutaneous T-cell lymphoma (CTCL) shares clinical similarities with AD and is also associated with a high prevalence of Staphylococcus aureus (S. aureus) colonisation. However, the mechanisms driving skin barrier damage in CTCL and the contribution of bacteria remain poorly understood.
Methods
We investigate how the interplay between S. aureus (and staphylococcal enterotoxins (SEs)) and primary malignant- and non-malignant T cells affects keratinocyte expression of skin barrier proteins; in vitro, in an EL4 murine lymphoma model of bacteria-driven tumour progression, and in CTCL patient lesions colonised with SE-producing S. aureus before and after bacterial eradication by antibiotic treatment.
Results
S. aureus and SEs activate malignant and non-malignant T cells to release barrier-repressing cytokines, including IL-4, IL-13, IL-22, and OSM, and JAK-dependent downregulation of filaggrin and loricrin in keratinocytes. In the EL4 model, bacteria-colonised tumour-bearing mice show significant filaggrin loss in tumour-adjacent epidermis, whereas antibiotic-treated mice maintain near-normal expression. Clinically, antibiotic eradication of SE-producing S. aureus partially restores filaggrin and loricrin expression in three of four patients, paralleling reduced inflammatory signalling.
Conclusions
SE-producing S. aureus promotes skin barrier impairment in CTCL through cytokine-driven, JAK-dependent repression of structural proteins in keratinocytes. These findings identify microbial–immune crosstalk as a contributor to CTCL skin pathology and provide mechanistic rationale for strategies targeting S. aureus colonisation as adjunctive therapy in CTCL.